Synthesis, physical-chemical and biological properties of 1,8-disubstituted of theobromine. ІV. 8-R-thioderivatives of 1-p-methylbenzyltheobronine - D. G. Ivanchenko (Zaporozhye State Medical University, 2015)
The problem of biologically active compounds searching amidst xanthine derivatives is a crucial one and is an issue for long-term investigation. Aim. In order to search for new biologically active compounds among xanthine derivatives, 8-R-thioderivatives of 1-p-methylbenzyltheobronine, undescribed earlier have been synthesized. Methods and results. Heating of 1-p-methylbenzyl-8-thiotheobromine with 2-bromo-4'-chloroacetophenone in aqueous ethanol leads to the formation of 1-p-methylbenzyl-8-[2-(4-chlorophenyl)-2-oxoethyl]thiotheobromine. Interaction of 8-thiotheobromine with chloroacetic acid methyl ester has lead to formation of (1-p-methylbenzyltheobromine-8-yl)thioacetic acid methyl ester. Structure of synthesized compounds has been definitely proved by NMR-spectroscopy. The acute toxicity, diuretic and antimicrobial activities of the obtained compounds have been explored. Conclusion. Priorities for further search of biologically active compounds in a range of xanthine derivatives have been set out.